Phase 1 Safety and Immunogenicity Evaluation of a Multiclade HIV-1 Candidate Vaccine Delivered by a Replication-Defective Recombinant Adenovirus Vector - Catanzaro, Andrew T. (2006)
BACKGROUND: The development of an effective human immunodeficiency virus (HIV) vaccine is a high global priority. Here, we report the safety, tolerability, and immunogenicity of a replication-defective recombinant adenovirus serotype 5 (rAd5) vector HIV-1 candidate vaccine. METHODS: The vaccine is a mixture of 4 rAd5 vectors that express HIV-1 subtype B Gag-Pol fusion protein and envelope (Env) from subtypes A, B, and C. Healthy, uninfected adults were randomized to receive 1 intramuscular injection of placebo (n = 6) or vaccine at dose levels of 10(9) (n = 10), 10(10) (n = 10), or 10(11) (n = 10) particle units and were followed for 24 weeks to assess immunogenicity and safety. RESULTS: The vaccine was well tolerated but was associated with more reactogenicity at the highest dose. At week 4, vaccine antigen–specific T cell responses were detected in 28 (93.3%) and 18 (60%) of 30 vaccine recipients for CD4(+) and CD8(+) T cells, respectively, by intracellular cytokine staining assay and in 22 (73%) of 30 vaccine recipients by enzyme-linked immunospot assay. Env-specific antibody responses were detected in 15 (50%) of 30 vaccine recipients by enzyme-linked immunosorbant assay and in 28 (93.3%) of 30 vaccine recipients by immunoprecipitation followed by Western blotting. No neutralizing antibody was detected. CONCLUSIONS: A single injection induced HIV-1 antigen–specific CD4(+) T cell, CD8(+) T cell, and antibody responses in the majority of vaccine recipients. This multiclade rAd5 HIV-1 vaccine is now being evaluated in combination with a multiclade HIV-1 DNA plasmid vaccine.